PENDAYAGUNAAN TEKNOLOGI INFORMASI DALAM PEMBERDAYAAN MASYARAKAT UNTUK MENGAWASI BEKERJANYA SISTEM PERADILAN PIDANA DI JAWA TENGAH - Agus Raharjo; Sunaryo Sunaryo; Nurul Hidayat (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Criminal Justice System did an approach of system. Focus of this research is effort to make a society participation model in observation to the working of criminal justice system. Method which used in this research is law as action is social science study which is non-doctrinal and hake the character of empiric. Experimentation test to made software to be done to find really exactly model. Criminal Justice System has criminogen characteristic, and this is one of the factor causing society participation level to enforcement of law in Indonesia lower. Effort to improve society participation in this case use information technology which in the form of ready of software able to be accessed by whosoever and wherever. This effort expect also can improve image of enforcement of law which till now is bad. Keyword : Criminal justice system, community empowerment, community participation, information technology